1993
DOI: 10.1165/ajrcmb/8.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Activated T Lymphocytes, Eosinophils, and Cytokine mRNA Expression for Interleukin-5 and Granulocyte/Macrophage Colony-stimulating Factor in Bronchial Biopsies after Allergen Inhalation Challenge in Atopic Asthmatics

Abstract: Immunohistology and in situ hybridization were used to evaluate the presence, activation status, and cytokine mRNA profile of cells in the bronchial mucosa during human allergen-induced asthma. Fifteen atopic asthmatic subjects underwent inhalation challenge with allergen and with allergen diluent, performed in random order separated by an interval of at least 3 wk. Bronchial biopsies were obtained 24 h after challenge. Immunostaining revealed increases in the numbers of secreting eosinophils (EG2+; P < 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
152
3
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(162 citation statements)
references
References 48 publications
5
152
3
2
Order By: Relevance
“…In cases of fatal asthma, the numbers of eosinophils were more closely related to the number of lymphocytes than in the nonfatal asthma and control cases. Numerous studies [3,12,15,16,19,20,24,[32][33][34] have shown increased numbers both of lymphocytes and eosinophils in asthmatic airways, although not over the range of asthma severity and airway sizes sampled in this study. It has been suggested that cell/ endothelial adhesion mechanisms and chemoattractant cytokines [35][36][37][38] may provide a common pathway of extravasation for lymphocytes and eosinophils at sites of inflammation.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In cases of fatal asthma, the numbers of eosinophils were more closely related to the number of lymphocytes than in the nonfatal asthma and control cases. Numerous studies [3,12,15,16,19,20,24,[32][33][34] have shown increased numbers both of lymphocytes and eosinophils in asthmatic airways, although not over the range of asthma severity and airway sizes sampled in this study. It has been suggested that cell/ endothelial adhesion mechanisms and chemoattractant cytokines [35][36][37][38] may provide a common pathway of extravasation for lymphocytes and eosinophils at sites of inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…Immunohistochemical techniques have identified the CD4+ subset of T-lymphocytes in the airways of patients with asthma, and have demonstrated that these lymphocytes and eosinophils express markers of functional activation to a greater extent than those from nonasthmatic subjects [11,12,15,16].…”
mentioning
confidence: 99%
“…1,2 Bronchoalveolar lavage (BAL) T cells from human asthmatics have been reported to express elevated levels of IL-4 and IL-5 mRNA. 3,4 In addition, an inverse association between Th1 tuberculin responses and asthma has been observed. 5,6 Current treatments for asthma are not satisfactory, and disease prevention is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…T cells have an important role in sensitization and immune responses. They release IL-3, -4, and -5 and GM-CSF, a pattern compatible with predominant activation of the Th2-type cell population (5), suggesting that activated T cells may contribute to cause inflammation with eosinophil accumulation during allergen-induced asthma (6). Similar pathologic changes in the bronchus were also observed in nonatopic asthma (7).…”
mentioning
confidence: 67%
“…It is known that lymphocytes, especially Th2-type lymphocytes, infiltrate into the airway tissue in asthmatics (5,6). However, the mechanism of infiltration is not well-known.…”
Section: Discussionmentioning
confidence: 99%